Remarks at the Climate Action Summit 2016 - Kim, Jim Yong (World Bank, Washington, DC, 2019)
Jim Yong Kim, President of the World Bank Group, discussed the need to tackle climate change. What we need to do now is build unprecedented political action to fulfill the promises. He mentioned that climate volatility in places like the Sahel in Africa contribute to instability and fragility. He noted how renewable energy is replacing coal. He outlined the main principles of a plan to transform the world’s transport systems—calling it “sustainable mobility for all.” He harkened the need for “fierce urgency of now.”